GENDER AND THE ISSUES OF BIOSECURITY'S MANAGEMENT IN THE COMMUNITY: OVERVIEW FROM CASE STUDY IN BALI - Ni Gst.Ag.Gde Eka Martiningsih (International Journal of Applied Science and Sustainable Development (IJASSD), 2019)
Many differences between the philosophy of Hinduism in Bali and the religious understanding of the younger generation with the older generation. Where there has been a change because of the ritual performed by Hindus, especially among the younger generation. While on the other hand rituals by several groups including farmers (in the subak organization) is still something that is still being done and taboo to be broken. Just one case in Subak Wongaya Betan who still believes that the spirit of rituals is associated with their implementation in the field of agriculture (Martiningsih, 2011). The same phenomenon also happens in all around Indonesia such as in Eastern Indonesia. In some cases, the philosophy of community awareness in eastern Indonesia will drive a good impact on the quality of life of the community. The rituals based on the awareness of something profane which farmers believe determines the success of their farm. Subak Wongaya Betan still implements continuous rituals collectively and personally. These rituals are usually performed in the temple to water resources and the environment in areas of subak such as Subak Temple and family temple. In one growing season subak implement collective rituals such as (1) Mapag Toya (2) mesaba and nangluk merana . All of the rituals have to be conducted by subak's member in one season of plantation are around 12 rituals. In this case, the member of Subak presented the concept of rituals according to Hindu society and how the ritual activities can tighten the social relationship between the member of subak and the village's community. One of the advantages of this phenomena is when the spirit of ritual always stands in rural community engagement. The result of the case study in Eastern Indonesia on gender issues summaries that the role of woman still to improve especially in public role such as an accessibility of leadership, decision-making process.